Quantification of Epstein-Barr Virus and Human Cytomegalovirus in Chronic Periodontal Patients - Khosropanah, Hengameh (Jundishapur J Microbiol, 2015)
BACKGROUND: Although studies focused mainly on the identification of periopathogenic bacteria, recent reports have suggested that various herpes viruses may also be involved in the occurrence and progression of different forms of periodontal diseases. OBJECTIVES: This study aimed to compare the prevalence and load of Epstein-Barr Virus (EBV) and Human Cytomegalovirus (HCMV) in subgingival tissue specimens between chronic periodontitis and healthy sites. PATIENTS AND METHODS: A total of 60 samples from the systematically healthy patients with chronic periodontitis participated in this study (mean age, 35 ± 7). Clinical periodontal evaluation included the plaque index (PI) (Loe and Silness), bleeding on probing (BOP) (O’Leary), bleeding index, periodontal pocket depth (PPD) and clinical attachment level measurement. Tissue specimens harvested from > 6 mm periodontal pockets and from ≤ 3 mm sulcus depth in a quadrant of the same patient using periodontal curettes. Moreover, the unstimulated whole saliva was gathered as a shedding medium. A Taq-man Real-Time Polymerase Chain Reaction assay was used to identify genomic copies of periodontal HCMV and EBV. Data were analyzed by the Wilcoxon-signed ranks and Friedman tests using the SPSS 16 software. RESULTS: Out of 60 samples of subgingival tissues taken from the patients with chronic periodontitis, EBV count was the highest in saliva and the least in the tissue sample with PD < 3 mm (P < 0.05). The highest HCMV count was in saliva and tissue samples with PD > 6 mm (P < 0.05). CONCLUSIONS: According to the results of this study, quantification of HCMV and EBV observed in this study is high in periodontal tissue samples of severe chronic periodontitis.